THE SOCIAL-PEDAGOGICAL NECESSITY OF PEDAGOGICAL COMMUNICATIVE COMPETENCE IN THE MODERN EDUCATIONAL PROCESS - Janonova Sitora Berdinazarovna, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In the conditions of rapid socio-economic change, globalization, and the digital transformation of education, the professional role of the teacher is undergoing significant redefinition. Contemporary education systems increasingly emphasize not only the transmission of academic knowledge but also the formation of socially active, communicatively competent, and value-oriented individuals. Within this context, teachers’ communicative competence becomes a key factor determining the effectiveness of pedagogical interaction and the quality of educational outcomes. This article provides a comprehensive theoretical analysis of the socio-pedagogical necessity of a teacher’s communicative competence in the modern educational process. The study is based on an integrative methodological framework combining theoretical analysis, comparative pedagogy, and systemic-structural approaches. The paper identifies the structural components of communicative competence, reveals its core socio-pedagogical functions, and substantiates its role in integrating education and upbringing. The results confirm that communicative competence constitutes a fundamental professional quality of teachers and a strategic resource for improving educational effectiveness in contemporary society.